Genetic variability of five indigenous Ethiopian cattle breeds using RAPD markers - Hassen, F.; Bekele, E.; Ayalew, W.; Dessie, Tadelle (2007)
Genetic diversity is the basis for present day diversified living systems and future genetic improvement needs. This diversity should be properly utilized, improved and conserved. Conservation and improvement strategies ought to be based on proper genetic characterization in association with phenotypic characterization. The objective of this work was to assess between and within breed genetic variability of five indigenous Ethiopian cattle breeds (Horro, Sheko, Arsi, Abigar and Guraghe highland) using RAPD markers. The Guraghe highland and Arsi breeds fall under Zebu breed group, the Sheko come from Humpless Shorthorn, the Abigar from the Sanga group and the Horro from Zenga group. Genetic relationships were estimated using three primers which produced 33 loci. The gene diversity obtained in this studywas found to be moderate and Analysis of MolecularVariance revealed that within breed genetic variation is much higher than that between breeds. Except few cases, genetic differentiation was highly significant. The smallest genetic divergence was between Guraghe highland and Abigar followed by Guraghe highland and Arsi. Sheko, historically considered to be humpless shorthorn, formed a distinct cluster whereas the remaining breeds formed another cluster. The RAPD markers were found to be useful to distinguish the breeds studied, but they failed to differentiate between Guraghe Highland and Abigar as they did thetwo zebu breeds -Guraghe Highland and Arsi. The Pearson's correlation between genetic and geographic distances (r = 0.22) was found to be statistically insignificant (P > 0.05).